Early assessment of circulating tumor DNA after curative‐intent resection predicts tumor recurrence in early‐stage and locally advanced non‐small‐cell lung cancer. Issue 2 (31st October 2021) - Waldeck, Silvia; Mitschke, Jan; Wiesemann, Sebastian; Rassner, Michael; Andrieux, Geoffroy; Deuter, Max; Mutter, Jurik; Lüchtenborg, Anne‐Marie; Kottmann, Daniel; Titze, Laurin; Zeisel, Christoph; Jolic, Martina; et al.
Abstract : Circulating tumor DNA (ctDNA) has demonstrated great potential as a noninvasive biomarker to assess minimal residual disease (MRD) and profile tumor genotypes in patients with non‐small‐cell lung cancer (NSCLC). However, little is known about its dynamics during and after tumor resection, or its potential for predicting clinical outcomes. Here, we applied a targeted‐capture high‐throughput sequencing approach to profile ctDNA at various disease milestones and assessed its predictive value in patients with early‐stage and locally advanced NSCLC. We prospectively enrolled 33 consecutive patients with stage IA to IIIB NSCLC undergoing curative‐intent tumor resection (median follow‐up: 26.2 months). From 21 patients, we serially collected 96 plasma samples before surgery, during surgery, 1–2 weeks postsurgery, and during follow‐up. Deep next‐generation sequencing using unique molecular identifiers was performed to identify and quantify tumor‐specific mutations in ctDNA. Twelve patients (57%) had detectable mutations in ctDNA before tumor resection. Both ctDNA detection rates and ctDNA concentrations were significantly higher in plasma obtained during surgery compared with presurgical specimens (57% versus 19% ctDNA detection rate, and 12.47 versus 6.64 ng·mL −1, respectively). Four patients (19%) remained ctDNA‐positive at 1–2 weeks after surgery, with all of them (100%) experiencing disease progression at later time points. In contrast, only 4 out of 12 ctDNA‐negative patients (33%) after surgery experienced relapse during follow‐up. Positive ctDNA in early postoperative plasma samples was associated with shorter progression‐free survival ( P = 0.013) and overall survival ( P = 0.004). Our findings suggest that, in early‐stage and locally advanced NSCLC, intraoperative plasma sampling results in high ctDNA detection rates and that ctDNA positivity early after resection identifies patients at risk for relapse. Abstract : ctDNA profiling in plasma revealed higher levels and detection rates of ctDNA during tumor resection as compared to pretreatment time points in patients with early‐stage or locally advanced NSCLC. Moreover, patients testing positive for ctDNA immediately after tumor resection had worse clinical outcomes than patients with undetectable ctDNA. Our research highlights the role of ctDNA assessment for guiding treatment in patients with respectable NSCLC.